Application of a montmorillonite clay modified with iron in photo-Fenton process: comparison with goethite and nZVI - de León, María A. (2015)
Iron pillared clay (Fe-PILC) was prepared from a montmorillonite and was characterized by scanning electron microscopy and X-ray fluorescence. Fe-PILC catalytic activity was evaluated in photo-Fenton processes applied to the degradation of 2-clorophenol. Different catalyst loads were assayed. The Fe-PILC allowed almost complete degradation of the contaminant. An increase in the contaminant degradation rate was observed, following leaching of iron during catalytic assays, which suggest the existence of a homogeneous photo-Fenton mechanism. The catalytic performance of the Fe-PILC was compared with that for goethite and zero valent iron nanoparticles. Differences were found regarding the achieved degradation levels, the efficiency in oxidant consumption, and the extension of iron leaching.